Relationship Between Coagulation and Prognosis of Gastric Cancer: A Systematic Review and Meta-Analysis - Lihui Zhu; Shuo Liu; Da Wang; Miao Yu; Hui Cai (Elsevier, 2024)
Background: The hypercoagulable state of cancer patients is associated with their high mortality rate. Coagulation indicators may have an important role in the prognosis of gastric cancer patients and deserve to be explored in various aspects. Objective: We conducted a meta-analysis to explore the correlation between coagulation and prognosis of gastric cancer. Methods: A comprehensive systematic search was conducted in PubMed, Embase, Web of Science databases, and the Cochrane Library up to February 16, 2024. Literature screening and data extraction were performed by two independent reviewers. The processed data we pooled using either a random-effects model or a fixed-effects model and finally described overall survival with a risk ratio (hazard ratio [HR]) and predicted the likelihood of different clinicopathological events with a dominance ratio (OR). Results: A total of 64 studies were screened for inclusion in the data analysis. Performing a meta-analysis of three indicators we derived that the risk of d-dimer (D-D), fibrinogen (FIB), and platelets (PLTs) were: HR = 1.85 (95% confidence interval [CI]: 1.59-2.15, N = 15), HR = 1.77 (95% CI: 1.57-1.99, N = 28), HR = 1.16 (95% CI: 1.12-1.21, N = 29). In addition to this, all three were associated with advanced clinicopathological stage (D-D: OR = 2.25, FIB: OR = 2.07, PLT: OR = 1.84), T stage (D-D: OR = 2.30, FIB: OR = 2.38, PLT: OR = 2.22) and lymph node metastasis (D-D: OR = 1.79, FIB: OR = 1.70, PLT: OR = 1.51). Conclusion: Overall, the findings suggest that the three indicators, D-D, FIB, and PLT count, have significant predictive value for the prognosis of gastric cancer. They were associated with an advanced clinicopathological stage and a high risk of lymph node metastasis.